Analisis Kinerja Keuangan dengan Menggunakan Metode Camel pada PT. Bank Rakyat Indonesia (PERSERO) TBK Periode 2019-2023 - Tasya Maharani; Burhanuddin Burhanuddin; Nurman Nurman; Anwar Anwar; Hety Budyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk uses the CAMEL method. The type of research used is descriptive with a quantitative approach. The sample in this study is in the form of financial statements of PT. Bank Rakyat Indonesia (Persero) Tbk for the period 2019-2023. The data collection technique used in this study is a documentation technique. The source of the data was obtained from the official website of the Indonesia Stock Exchange. The results show that the final value of CAMEL, which consists of capital, assets, management, earning, and liquidity in each period by multiplying the credit value of each ratio with the CAMEL weight that has been set by Bank Indonesia, is in the range of 81-100. Thus, it can be concluded that the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk using the CAMEL method during the 2019-2023 period is in a healthy predicate.